2008
DOI: 10.1124/mol.108.051334
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Small-Molecule Prohormone Convertase 2 Inhibitors

Abstract: The proprotein convertases are believed to be responsible for the proteolytic maturation of a large number of peptide hormone precursors. Although potent furin inhibitors have been identified, thus far, no small-molecule prohormone convertase 1/3 or prohormone convertase 2 (PC2) inhibitors have been described. After screening 38 small-molecule positional scanning libraries against recombinant mouse PC2, two promising chemical scaffolds were identified: bicyclic guanidines, and pyrrolidine bis-piperazines. A se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…These differences agree with results obtained for fluorogenic substrate cleavage, confirming that the ranking of the best PC2 inhibitors is 166830 Ͼ 166369 Ͼ 166829 for both proglucagon cleavages to immunoreactive glucagon and for pERTKR-AMC hydrolysis. We used the same assay to compare the pyrrolidine bis-piperazine 1435-6 compound, previously identified by our group as a potent PC2 inhibitor (Kowalska et al, 2009), with the present compounds. We found that the potency of compound 1435-6 in blocking PC2-mediated generation of immunoreactive glucagon from recombinant proglucagon was much weaker than that of 166830, 166369, and 166829 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These differences agree with results obtained for fluorogenic substrate cleavage, confirming that the ranking of the best PC2 inhibitors is 166830 Ͼ 166369 Ͼ 166829 for both proglucagon cleavages to immunoreactive glucagon and for pERTKR-AMC hydrolysis. We used the same assay to compare the pyrrolidine bis-piperazine 1435-6 compound, previously identified by our group as a potent PC2 inhibitor (Kowalska et al, 2009), with the present compounds. We found that the potency of compound 1435-6 in blocking PC2-mediated generation of immunoreactive glucagon from recombinant proglucagon was much weaker than that of 166830, 166369, and 166829 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PC2 is known to have a potent natural inhibitor in the form of the 7B2 carboxyl-terminal peptide (Apletalina et al, 2000a); it is also inhibited by the cystatin-related epididymal spermatogenic protein (Cornwall et al, 2003). The only previous report of small molecule PC2 inhibitors are certain pyrrolidine bis-piperazines and bicyclic guanidines, which inhibit this enzyme with micromolar potency (Kowalska et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations